1999
DOI: 10.1007/s000110050418
|View full text |Cite
|
Sign up to set email alerts
|

Diamine oxidase and catalase are expressed in the same cells but are present in different subcellular compartments in porcine kidney

Abstract: IntroductionDiamine oxidase (DAO; EC 1.4.3.6) catalyzes the oxidative deamination of histamine and other biogenic amines in a reaction that produces the corresponding aldehyde as well as ammonia and hydrogen peroxide [1]. Hydrogen peroxide is a highly reactive compound and may cause cellular damage if not scavenged appropriately [2]. Therefore, we reasoned that the hydrogen peroxide producing and degrading enzymes might be co-localized in mammalian tissues and analyzed the cellular and subcellular distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Concerning the alternative pathway of histamine catabolism, involving diamine oxidase, few immunohistochemical data are available. Although Schwelberger et al (1998Schwelberger et al ( ,1999 reported the presence of DAO in the intestine and proximal tubules in pig kidney, the immunohistochemical localization in other tissues remains unclear. Beaven (1982) suggested that the localization of DAO was restricted to the intestine, kidney, thymus, and placenta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the alternative pathway of histamine catabolism, involving diamine oxidase, few immunohistochemical data are available. Although Schwelberger et al (1998Schwelberger et al ( ,1999 reported the presence of DAO in the intestine and proximal tubules in pig kidney, the immunohistochemical localization in other tissues remains unclear. Beaven (1982) suggested that the localization of DAO was restricted to the intestine, kidney, thymus, and placenta.…”
Section: Discussionmentioning
confidence: 99%
“…Although there exist two main catabolic pathways for histamine in tissues, methylation by histamine N -methyltransferase (HMT; EC 2.1.1.8.) and oxidative deamination by diamine oxidase (DAO; EC 1.4.3.6) (Beaven 1982), information on the relative importance of each pathway to the catabolism of histamine in tissue as well as the cellular localization of these enzymes (Fukuda et al 1986;Schwelberger et al 1999) is limited.…”
mentioning
confidence: 99%
“…Diamine oxidase (DAO), which is an SSAO, is above all expressed in intestine, kidney and placenta. Its subcellular localization has been defined in porcine small intestine and kidney, where it is present in plasma‐membrane‐associated vesicles [59,60]. Lysyl oxidase is unique amongst the SSAO family of enzymes: although it is sensitive to SSAO inhibitors, its cofactor appears to be lysine tyrosylquinone rather than topaquinone (TPQ) [58].…”
Section: Factors Affecting the Relative Importance Of Amine Oxidases mentioning
confidence: 99%
“…The intolerance results from an imbalance between the uptake of histamine and the histamine-degrading enzyme diamine oxidase (DAO) (EC 1.4.3.22) [5]. Human DAO is a secretory enzyme that is located mainly in the small intestinal mucosa and the kidneys [3,6,7]. This enzyme catalyzes the oxidative deamination of histamine or other biogenic amines to the corresponding aldehydes, ammonia, and hydrogen peroxide [8].…”
Section: Introductionmentioning
confidence: 99%